Center variation in long‐term outcomes for socioeconomically deprived children. Issue 9 (4th March 2021) - Wadhwani, Sharad I.; Huang, Chiung‐Yu; Gottlieb, Laura; Beck, Andrew F.; Bucuvalas, John; Kotagal, Uma; Lyles, Courtney; Lai, Jennifer C.
Abstract : Neighborhood socioeconomic deprivation is associated with adverse outcomes after pediatric liver transplant. We sought to determine if this relationship varies by transplant center. Using SRTR, we included patients <18 years transplanted 2008–2013 (N = 2804). We matched patient ZIP codes to a deprivation index (range [0, 1]; higher values indicate increased socioeconomic deprivation). A center‐level patient‐mix deprivation index was defined by the distribution of patient‐level deprivation. Centers (n = 66) were classified as high or low deprivation if their patient‐mix deprivation index was above or below the median across centers. Center quality was classified as low or high graft failure if graft survival rates were better or worse than the overall 10‐year graft survival rate. Primary outcome was patient‐level graft survival. We used random‐effect Cox models to evaluate center‐level covariates on graft failure. We modeled center quality using stratified Cox models. In multivariate analysis, each 0.1 increase in the patient‐mix deprivation index was associated with increased hazard of graft failure (HR 1.32; 95%CI: 1.05, 1.66). When stratified by center quality, patient‐mix deprivation was no longer significant (HR 1.07, 95%CI: 0.89, 1.28). Some transplant centers care for predominantly high deprivation children and maintain excellent outcomes. Revealing and replicating these centers' practice patterns should enable more equitable outcomes. Abstract : The authors explore center‐level effects on outcomes for socioeconomically deprived children and find that certain centers are able to maintain excellent outcomes while caring for predominately socioeconomically deprived children.